DISCUSION DEL MOVIMIENTO CIRCULAR Y PRUEBA DIRECTA DE SU EXISTENCIA EN EL FLUTTER AURICULO CLINICA - PALLARES SODI, ERNESTO; CABRERA, ENRIQUE (Instituto de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1973)
Histochemical reactions for alkaline phosphatase and glycogen were done in 73 specimens of human endometrium obtained by biopsy Silver staining techniques for glycogen and Gomori's procedure for alkaline phophatase were favored in this study The amt of
ARCH INST CARDIOL MEX
Keywords: DISCUSION, MOVIMIENTO, CIRCULAR, PRUEBA, FLUTTER, AURICULO, CLINICA; CIENCIAS MEDICAS; MEDICINA INTERNA; CARDIOLOGIA